Transient electromagnetic-thermal nondestructive testing - He, Yunze; Gao, Bin; Sophian, Ali; Yang, Ruizhen (Elsevier, 2017)
Transient Electromagnetic-Thermal Nondestructive Testing: Pulsed Eddy Current and Transient Eddy Current Thermography covers three key areas of theories, methods and applications, primarily the multi-physics field, including eddy current, heat conduction and Infrared radiation for defect evaluation, lateral heat conduction, which is analyzed to detect parallel cracks, and longitudinal heat conduction, which is analyzed to detect depth defect, or that which is beyond skin depth.